Nanoscale agglomeration mechanisms of BF-DPB: BPyMPM donor-acceptor systems for organic optoelectronic devices - Merkel, Milena; Wiesener, Philipp; Schmidt, Robert; Shivhare, Rishi; Doltsinis, Nikos; Bratschitsch, Rudolf; Amirjalayer, Saeed; Vandewal, Koen; Mönig, Harry (Advanced functional materials, 2025)
The molecular order of the photo-active molecules in organic solar cells and exciplex organic light emitting diodes based on donor-acceptor mixed systems has major influence on the performance. However, it is usually investigated only by indirect measurements or simulations. Here, low-temperature scanning probe microscopy is used to directly image the molecular assembly, intermolecular bonding configuration, and domain interfaces of vacuum-deposited donor and acceptor molecules BF-DPB and BPyMPM on different single crystalline substrates with submolecular resolution. It is demonstrated that the position of the nitrogen atoms in the peripheric pyridine rings of BPyMPM molecules determines the occurrence of intermolecular C─H…N hydrogen bonds, metal coordination bonds, and related self-assemblies. Two dominating self-assembled structures of BF-DPB are found, based either on its cis or trans configuration. In general a distinct increase in disorder occurs at the BF-DPB:BPyMPM interface where scanning tunneling spectroscopy indicate an increase in the HOMO-LUMO gap at disordered agglomerates of BF-DPB. The crucial effect of the choice of substrate on the molecular order is illustrated. Photoluminescence measurements indicate a considerable increase in intersystem crossing in BF-DPB due to molecule-substrate interactions. These findings provide new insights for the targeted molecular design of active molecules and suitable contact layers in organic optoelectronic devices.